Analisis Pengaruh Hubungan Antar Manusia,Kondisi Fisik Lingkungan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Cheetham Garam Indonesia Di Kabupaten Nagekeo - Basri, Andi; Langga, Lambertus; Dua Mea, Maria Helena Carolinda (Program Studi Manajemen Universitas Flores, 2021)
This study aims to determine the effect of human relations, the physical condition of the work environment and workload on the performance of employees at PT. Indonesian salt cheetham in Nagekeo Regency. This type of research is causality research with a quantitative approach. The data analysis technique used is multiple linear regression analysis. The population in this study consisted of 102 people and a sample of 73 people who were obtained using Sugiono's table of provisions with an error rate of 10%. The sampling technique used random sampling.From the results of the development and testing of the instrument, a good questionnaire was produced (it fulfills the validity and reliability requirements). From the results of t statistical testing for the inter-human relationship variable, the physical condition of the work environment has a value of ?????????????????????????> ???????????????????????? and a significance value of <0.05, and the workload variable has a value of ????????????????????????? <???????????????????????? a significance value> 0.05. This shows that the inter-human relationship variables, the physical condition of the work environment have an effect on employee performance, while the workload variable has no effect on employee performance. In the F test results, with a value of ????????????????????????? = 29.296> F table = 2.74 and a significance value <0.05. This shows that the inter- human relationship variable (X1), the physical condition of the work environment (X2), and the workload (X3) simultaneously have an effect on employee performance (Y). For the adjusted R square value of 0.541 or 54%, this shows that the percentage of the analysis of the effect of human relations, the physical condition of the work environment and workload on employee performance is 54%. Meanwhile 46% is influenced by other factors that are not explained in this study.